Traces of Earthquake: Traumatic Life Experiences and Their Effects on Volunteer Nurses in the Earthquake Zone-An Interpretative Phenomenological Study - Cakiroglu, Oya Celebi; Unver, Gamze Tuncer; Cakiroglu, Suleyman (Wiley, 2025)
IntroductionIt is crucial to understand the effects that traumatic events related to natural disasters have on individuals in as much detail as possible. However, the literature investigating the traumatic life experiences of nurses, who play a key role in disaster management, is still limited.ObjectiveThe aim of this study was to explore in depth the traumatic life experiences of volunteer nurses who participated in relief efforts after two major earthquakes in the southeastern region of T & uuml;rkiye.MethodsThis qualitative study was conducted using a phenomenological design. The study sample consisted of 16 nurses selected by the purposive and snowball sampling methods. The data were evaluated using interpretative phenomenological analysis in the Maxqda 2020 program.ResultsFour themes were generated: (1) shocking facts, (2) coping methods, (3) traumatic stress reactions, and (4) traumatic growth.ConclusionWhile traumatic life experiences in the earthquake area led to acute stress reactions in the volunteer nurses, these experiences also contributed to their traumatic growth and development. Healthcare managers and policymakers should develop comprehensive strategies and intervention programs to safeguard the mental health of nurses in the context of natural disasters. It may also be useful to improve clinical education programs and support systems by reviewing international policies and procedures.
Keywords: Natural Disasters; Earthquakes; Nursing; Qualitative Research; Traumatic Stress; Traumatic Growth